Eksperimentasi Metode Terapi dengan Musik untuk Pasien Skizofrenia di RSJD Surakarta - Elya Nindy Alfionita; Bondet Wrahatnala (Jurnal Kajian Seni, 2019)
AbstractThe object of study "Experimentation With Music Therapy Method for the Treatment of Schizophrenia in a Psychiatric Hospital Area Surakarta" aims to uncover and describe the shape of healing method performed by a team of occupational RSJD Surakarta to patients with schizophrenia. The research appears as the existence of a form of musical phenomenon in which there are adaptations as a form of healing effort to psychiatric patients with schizophrenia. Schizophrenia is classified as severe mental disorders ( psychotic ) that attacks the majority of patients at the Mental Hospital of Surakarta. Besides occupational team also did a musical experimentation that aims to find the song material in accordance with the psychological and social conditions of patients with schizophrenia This study uses the approach of ethnomusicology delivered with the theory and the concept of the four imperatives Talcot Parson as follows; adaptation, goal Attaintment, integration, and latency. Then the author uses to do research in qualitative ethnographic methods using techniques literature study, observation, and interviews. The results of the analysis found that occupational therapy is music with a tempo of 60-75 bpm is able to stabilize the emotions in schizophrenic patients. Occupational therapy with the tempo of the achievements gained 75% of the experimentation results obtained through the four models of the patient. Keywords: Schizophrenia, Occupational Therapy, Regional Psychiatric Hospital Surakarta.